Identifikasi Tugas Sekretaris Pada Bank Nagari Cabang Utama Padang Sumatera Barat - Shelby Edinov (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
The secretary assists the leader in carrying out activities. At Bank Nagari, Main Branch Padang, West Sumatra, the chief secretary has routine duties, namely receiving incoming letters and dispositions to branch heads and distribution to related work units, carrying out mail and document storage, managing reception, receiving calls and answering calls, maintaining and managing harmony and cleanliness . Special tasks, namely having the task of managing and organizing the implementation of meetings, taking care of the leadership's official travel, providing information about the leadership. Special duties, namely having the task of providing and maintaining equipment, as a second source of information. The receptionist's job is to receive and answer telephones, receive guests and provide the best service. Social tasks have the task of holding family gatherings, sending congratulations, sending and replying to congratulations. Incidental tasks, namely having the task of representing the leadership in meetings. The business meeting task has the task of determining the time and place of the business meeting, providing equipment for the meeting, and preparing snacks. Creative tasks have the task of mastering the skills of using office equipment and preparing souvenirs for leaders and their organizational relations.